Review of the hyperiidean amphipod family Lycaeidae Claus, 1879 (Crustacea: Amphipoda: Hyperiidea) - Zeidler, Wolfgang (Zootaxa, 2021)
This is the first comprehensive taxonomic review of the family Lycaeidae. This study is based primarily on the extensive collections of the Natural History Museum, Denmark (NHMD, formerly ZMUC) and the US National Museum of Natural History, Smithsonian Institution, Washington DC, USA (USNM), and on additional material from the South African Museum (SAM) and in the South Australian Museum (SAMA). The two currently recognized genera in the family, Lycaea Dana, 1852 and Simorhynchotus Stebbing, 1888, are maintained with the latter still regarded monotypic with S. antennarius (Claus, 1871). Characters used to distinguish species in the past are re-evaluated in order to determine their validity. There are 15 nominal species of Lycaea in the literature, excluding Pseudolycaea pachypoda Claus, 1879 and Metalycaea globosa Stephensen, 1925. Pseudolycaea Claus, 1879 is regarded a synonym of Lycaea, as confirmed by this study, and M. globosa is a junior synonym of L. serrata Claus, 1879, as demonstrated by an examination of the type material. Of the remaining nominal species many have been synonymized with L. pulex Marion, 1874 in the past, often based on erroneous literature references. Thus, the taxonomic status of all nominal species was redetermined by the examination of type material or from the original literature reference if type material could not be found. In conclusion, ten species of Lycaea are recognized as valid, including three described as new. Lycaea bovallii Chevreux, 1900 is determined to be a valid species with the following as junior synonyms, L. gracilis Spandl, 1924, L. bajensis Shoemaker, 1925 and L. bovallioides Stephensen, 1925. It seems to be widely distributed and relatively common in the tropical regions of all the world’s oceans, including the Mediterranean Sea. The other species recognized as valid are L. lilia Volkov, 1982; L. nasuta Claus, 1879; L. pachypoda (Claus, 1879); L. pulex Marion, 1874 (L. robusta Claus, 1879, L. similis Claus, 1879 and L. pauli Stebbing, 1888 regarded junior synonyms); L. serrata Claus, 1879 and L. vincentii Stebbing, 1888 (Amphipronoe longicornuta Giles, 1888 a junior synonym). In addition, three species are described as new to science; L. intermedia sp. nov., L. proserrata sp. nov. and L. osbornae sp. nov. All were found in the tropical regions of the Atlantic, Pacific and Indian Oceans; the former two are relatively common and widespread. All species are described and illustrated and a key is provided to facilitate their identification.